CITRA PEREMPUAN JAWA DALAM NOVEL GARIS PEREMPUANKARYA SANIE B. KUNCORO DAN IMPLIKASINYA TERHADAP PEMBELAJARAN BAHASA INDONESIA DI SMA - Alfi Nur Afidah; Tri Mulyono; Afsun Aulia Nirmala (Universitas Galuh, 2020)
ABSTRACTThe purpose of this study was to describe the image of Javanese women contained in the novel Garis Perempuan by Sanie B. Kuncoro and the implications of learning the image of Javanese women